Evolution of Land Use Landscape Patterns in Karst Watersheds of Guizhou Plateau and Its Ecological Security Evaluation - Yue Li; Huacai Geng (Land, 2022)
Landscape ecological safety is of great significance in maintaining ecological balance, ecological protection, economic development, and promoting the sustainable use of regional land resources. This study collects three-phase remote sensing (RS) image data of 2000, 2010, and 2020 to elucidate the spatial and temporal changes in land use of the Guizhou Plateau Karst Watershed. We construct a landscape ecological security index using the ArcGIS and landscape pattern index method. With the spatial autocorrelation theory, we analyze the evolution of watershed landscape patterns and changes in characteristics of ecological security. The results show that the cultivated land is being converted to construction land in the watershed from 2000 to 2020. The percentage of the patch area of the constructed land is increasing. However, the patch cohesion of the cultivated land, grassland, and watershed is decreasing. The ecological safety of the Nanming River Basin landscape is in a positive trend, clustering in the central urban areas. The growth rate of the landscape ecological safety index increased by 5.80% from 2000 to 2020, and the aggregation of the ecological safety index was dominated by high–high aggregation and low–low aggregation, which was spatially positively correlated with the spatial aggregation effect. The findings provide a scientific reference for managing ecological balance and optimizing the land resource allocation in karst watersheds.